SPG5 and multiple sclerosis: clinical and genetic overlap?. (15th September 2015) - Criscuolo, C.; Carbone, R.; Lieto, M.; Peluso, S.; Guacci, A.; Filla, A.; Quarantelli, M.; Lanzillo, R.; Brescia Morra, V.; De Michele, G.
Abstract : Background: Autosomal recessive (AR) spastic paraplegia type 5 (SPG5) is due to mutations in the CYP7B1 gene, encoding for the cytochrome P450‐7B1, responsible for oxysterols 7 α ‐hydroxylation. Oxysterol/cholestenoic acids pool plays a role in motor neuron survival and immune response. SPG5 is characterized by white matter abnormalities at brain resonance imaging (MRI). In view of clinical presentation and MRI findings, multiple sclerosis (MS) is a possible differential diagnosis of SPG5. This study aimed to evaluate the frequency of CYP7B1 mutations in patients with MS. Methods: One hundred and seventeen MS patients with clinical spastic paraplegia or possible AR transmission were selected for the mutational screening. Results: Forty‐three patients had primary progressive, 26 relapsing remitting, 26 secondary progressive, and 22 relapsing progressive MS clinical course. No CYP7B1 homozygous mutations were identified. Two novel variants and one pathogenic mutation were found at heterozygous state. Conclusions: The two novel variants cosegregated with pyramidal signs and autoimmune diseases suggesting that they might be susceptibility factors. Reduced cytochrome P450‐7B1 enzymatic activity could alter the balance among neurotoxic and neuroprotective oxysterols promoting motor neuron degeneration and/or immune response.